Nutrition and Swallowing Therapy in Head and Neck Cancer: Utilization of Care and Preventative Efficacy. (17th November 2018) - Perlow, Haley K.; Ramey, Stephen J.; Farnia, Benjamin; Silver, Ben; Kwon, Deukwoo; Chinea, Felix M.; Sotnick, Sandra C.; Klein, Lesley B.; Elsayyad, Nagy; Samuels, Michael A.; Freedman, Laura; Yechieli, Raphael; et al.
Abstract: Purpose: To examine the impact of ethnicity, Spanish language preference, socioeconomic status, and treatment setting on utilization of supportive services before radiotherapy (RT) among head and neck cancer patients and to determine whether a lack of these services is associated with an increased rate of adverse events. Methods and Materials: Demographic, staging, and treatment details were retrospectively collected for patients treated at a safety-net hospital ( n  = 56) or adjacent private academic hospital ( n  = 183) from January 1, 2014, to June 30, 2016. Supportive care services evaluated were limited to speech/swallowing therapy and nutrition therapy. Adverse events and performance measures examined included weight loss during RT, gastric tube placement, emergency department visits, hospital admissions, and missed RT days. Results: On multivariable analysis, patients receiving treatment at the safety-net hospital were less likely to receive speech/swallowing services. Receiving speech/swallowing therapy before treatment was associated with less weight loss during treatment, and in conjunction with nutrition therapy, was associated with fewer missed RT days. Conclusion: Safety-net hospital treatment was associated with a lack of utilization of pre-RT speech/swallowing therapy which in turn was associated with increased weight loss. Interventions aimed at improving utilization of these services would improve treatment tolerance and patient outcomes.